Professional artistic training of students in teaching painting - Ayad Taama (Global Prosperity, 2023)
The article analyzes the professional and artistic training of students in teaching painting. It was determined that teaching painting is carried out on the basis of studying the basic techniques and means of creating a composition on the plane of the pictorial form, transferring its dimensions, volume, textural and spatial qualities. In this regard, a student should be able to rationally and effectively build objects, correctly convey their proportions, volumetric, constructive, material, spatial qualities, this indicates that, in addition to knowledge about the theory of drawing and composition, it is important to acquire knowledge of practice about various painting materials, to know the rules of realistic and decorative depiction of reality. In addition, in the process of teaching painting, it is necessary to apply a system of various teaching methods, namely: explanatory and illustrative method, research method and method of sequential formation of painting skills. In painting classes, students should master the skills of using the laws of perspective (linear and aerial), composition, and the correct optical mixing of colors in the practical field. And the acquisition of knowledge about the laws of color mixing optimizes the practical activities of the future specialist, helps inform students about the laws of color science in an easier way, which helps make painting classes more interesting and expressive (bright). The conclusions were formed that in the process of teaching painting, students gradually acquire knowledge, abilities and skills in the field of painting, study the main laws and features of the reproduction of the surrounding reality with the help of color, in addition, they become aware of the laws of color construction of a realistic form, learn the methods and means of construction on a plane pictorial form with the transfer of proportions, constructive, three-dimensional, material and spatial properties. Studying the theory and practice of painting makes it possible to find various approaches to solving creative tasks of varying complexity, promotes the stimulation of artistic and cognitive interests and needs, the development of intellectual and visual abilities, spiritual and value orientations, the ability to communicate, self-realization of students, contributes to the development of an individual professional work style.